MEKANISME PENGELOLAAN DANA BADAN PENYELENGGARA JAMINAN SOSIAL KESEHATAN - Fakhruddin, Akhmad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
Planning and implementation mechanism are part of fund management mechanism. The purpose of this researchis to find out planning preparation mechanism, health insurance fund management that comes from society andgovernment, and the implementation of these activities.The result of the research shows that: 1) planning hasbeen carried out by preparing vision, mission and objectives. In order to achieve vision, mission and objectivesproperly, Social Security Agency (BPJS) of Health Regional Division VII East Java Province sets the budgetwork plan every years. The system is bottom up, 2) fund management process in Social Security Agency (BPJS)of health regional division VII East Java Province is the funds that come from the member and government fund.The fund that has been collected will be separated into 2 in its management, i.e.: Social Security Agency (BPJS)fund and Social Security Fund (DJS), 3) in its implementation, Social Security Agency (BPJS) of the HealthRegional Division VII East Java Province does not levy on profit (non profit oriented) and the implementationhas been carried out in accordance with the determined time schedule that is in accordance with the decree ofDirectorKeywords: Planning, Fund Management, and Implementation.